Nationwide population-based cohort study of uterine rupture in Belgium: results from the Belgian Obstetric Surveillance System - Vandenberghe, G (BMJ Open, 2016)
OBJECTIVES: We aimed to assess the prevalence of uterine rupture in Belgium and to evaluate risk factors, management and outcomes for mother and child. DESIGN: Nationwide population-based prospective cohort study. SETTING: Emergency obstetric care. Participation of 97% of maternity units covering 98.6% of the deliveries in Belgium. PARTICIPANTS: All women with uterine rupture in Belgium between January 2012 and December 2013. 8 women were excluded because data collection forms were not returned. RESULTS: Data on 90 cases of confirmed uterine rupture were obtained, of which 73 had a previous Caesarean section (CS), representing an estimated prevalence of 3.6 (95% CI 2.9 to 4.4) per 10 000 deliveries overall and of 27 (95% CI 21 to 33) and 0.7 (95% CI 0.4 to 1.2) per 10 000 deliveries in women with and without previous CS, respectively. Rupture occurred during trial of labour after caesarean section (TOLAC) in 57 women (81.4%, 95% CI 68% to 88%), with a high rate of augmented (38.5%) and induced (29.8%) labour. All patients who underwent induction of labour had an unfavourable cervix at start of induction (Bishop Score ≤7 in 100%). Other uterine surgery was reported in the history of 22 cases (24%, 95% CI 17% to 34%), including 1 case of myomectomy, 3 cases of salpingectomy and 2 cases of hysteroscopic resection of a uterine septum. 14 cases ruptured in the absence of labour (15.6%, 95% CI 9.5% to 24.7%). No mothers died; 8 required hysterectomy (8.9%, 95% CI 4.6% to 16.6%). There were 10 perinatal deaths (perinatal mortality rate 117/1000 births, 95% CI 60 to 203) and perinatal asphyxia was observed in 29 infants (34.5%, 95% CI 25.2% to 45.1%). CONCLUSIONS: The prevalence of uterine rupture in Belgium is similar to that in other Western countries. There is scope for improvement through the implementation of nationally adopted guidelines on TOLAC, to prevent use of unsafe procedures, and thereby reduce avoidable morbidity and mortality.